2021
DOI: 10.1016/j.radcr.2021.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Malignant triton tumor of the anterior mediastinum: a rare tumor in a rare location

Abstract: Malignant triton tumors are an extremely aggressive form of malignant peripheral nerve sheath tumor that display rhabdomyosarcomatous features. While these tumors are extremely rare, they have a much higher incidence in patients with neurofibromatosis-1. We present a case of a 64-year-old male with neurofibromatosis-1 who presented to the hospital with sudden worsening of shortness of breath and dysphagia to solids. Radiological examination revealed a large mass in the anterior mediastinum causing significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…MTTs represent a rare subtype of MPNSTs that upon inspection are sturdy, large, grayish tan neoplasms with intrinsic zones of hemorrhage and necrosis [ 8 , 9 , 10 , 11 ]. They are very rare, since MPNSTs comprise between 5% and 10% of all soft tissue sarcomas, while MTTs represent less than 10% of all MPSNTs .…”
Section: Types Of Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…MTTs represent a rare subtype of MPNSTs that upon inspection are sturdy, large, grayish tan neoplasms with intrinsic zones of hemorrhage and necrosis [ 8 , 9 , 10 , 11 ]. They are very rare, since MPNSTs comprise between 5% and 10% of all soft tissue sarcomas, while MTTs represent less than 10% of all MPSNTs .…”
Section: Types Of Tumorsmentioning
confidence: 99%
“…Chronic lymphocytic leukemia and diffuse B cell lymphomas may also occur in these patients, although these associations are exceptionally rare [ 6 , 7 ]. Other cancers more commonly encountered in patients with NF1 include the malignant triton tumors (MTTs), which are a rare variant of MPNSTs [ 8 , 9 , 10 , 11 ]. The malignant transformation of spinal low-grade astrocytomas and the appearance of cerebral glioblastomas associated with NF-1 have also been documented [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…We compiled data on reported cases of MTT in the recent 6 years (2018–2023, Table 1). 1,6–38 There were totally 37 cases with a mean age of 39.4 years (range 8 months old–75 years old), including 24 male and 13 female patients. Eleven cases originated in the abdomen (30%), 10 cases in the head and neck (27%), 8 cases in the thoracic cavity (21%), 6 cases in the limbs (16%), 1 case in the spine (3%), and 1 case in the buttocks (3%).…”
Section: Results Of Literature Reviewmentioning
confidence: 99%
“…A range of cases presentation in the literature we reviewed describe the imaging manifestations (including CT and MRI) correlated with MTT: giant lump, heterogeneity, irregular margins, intratumoral hemorrhage, necrosis, lobulation, calcifications, heterogenous enhancement on postcontrast CT or MRI, hypointense/isointense T1WI and hyperintense T2WI signal on MRI, and diffusion restriction on DWI and ADC 1,8–32,39,40 . Zain et al 20 and Li et al 29 had reported similar conclusions, Li et al pointed out some characteristics common to MTTs and MPNSTs, including ill‐defined margin, intratumoral lobulation, peripheral edema, calcifications, and destruction of adjacent bone tissues. In our case, it manifested as a heterogeneous giant mass with unclear border in ultrasonography, long T1 and T2 signals on MRI, marginal lobulation, and multiple metastases on PET‐CT.…”
Section: Discussionmentioning
confidence: 99%